José Celestino Mutis, the ants, and Pheidole mutisi sp. nov. - FERNÁNDEZ, FERNANDO; WILSON, EDWARD O. (Revista Colombiana de Entomología, 2008)
A new ant species, Pheidole mutisi (Hymenoptera: Formicidae: Myrmicinae), is described in honor of José Celestino Mutis, the Neogranadian “Wiseman” who conducted the first studies on ants in the New World, although his writings on the subject remained unknown for many years. Here we offer some general comments about Mutis’ myrmecological studies. This publication commemorates the 200th anniversary of Mutis’ death. The new species is characterized by its smooth, shiny body without standing pilosity (major) and long propodeal spines (major and minor).